Endoplasmic reticulum stress‐mediated autophagy protects against lipopolysaccharide‐induced apoptosis in HL‐1 cardiomyocytes. Issue 10 (14th July 2014) - Zou, Xiaojing; Xu, Jianjun; Yao, Shanglong; Li, Jian; Yang, Yan; Yang, Le
<x xml:space="preserve">Abstract</x> New Findings What is the central question of this study? Cardiac dysfunction in sepsis is associated with apoptosis of cardiomyocytes. Is endoplasmic reticulum (ER) stress induced in lipopolysaccharide (LPS)‐treated cardiomyocytes? Does ER stress‐induced autophagy protect against LPS‐induced apoptosis of cardiomyocytes? What is the mechanism in detail? What is the main finding and its importance? Our results indicate that ER stress is activated and mediates autophagy in LPS‐treated murine atrium‐derived cardiac HL‐1 cells. Protein kinase regulated by RNA‐like ER‐associated kinase (PERK), one arm of ER stress, is involved in protecting against LPS‐induced apoptosis of HL‐1 cells by promotion of autophagy. Apoptosis of cardiomyocytes limits the contractile efficiency of the heart during sepsis. Prosurvival autophagy has been proposed as a novel mechanism to maintain normal heart function. Here, we demonstrated that autophagy was activated in lipopolysaccharide (LPS)‐treated HL‐1 cells, and it counteracted the LPS‐induced apoptosis. We investigated further the mechanism by which LPS triggered autophagy in HL‐1 cells. We discovered that endoplasmic reticulum (ER) stress played an important role in LPS‐triggered autophagy. The ER activated a survival pathway through the ER‐localized transmembrane protein PERK, which was essential for LPS‐induced autophagy. Lipopolysaccharide increased expression of GRP78, phosphorylated PERK and phosphorylated eukaryotic initiation factor 2α. Similar results were observed after administration of tunicamycin, a well‐known ER stressor. Most importantly, we found that 4‐phenylbutyrate, an inhibitor of ER stress, suppressed LPS‐activated autophagy in the presence of LPS in HL‐1 cells. The same results were observed after small interfering RNA‐mediated silencing of PERK protein. We also noticed that LPS‐induced apoptosis appeared early, at 4 h. Our findings revealed that PERK, one arm of ER stress, facilitated survival of LPS‐treated HL‐1 cells by promoting autophagy, and could serve as a potential therapeutic strategy to alleviate septic myocardial dysfunction.